Stand up and Fight: A Case Study of a Professional Rugby Club Negotiating a COVID-19 Crisis, a Talent Development Perspective - Ian Costello; Sarahjane Belton; Áine MacNamara (MDPI AG, 2022)
A wealth of literature examines the role of challenge from an individual psychological perspective, but research investigating how a talent development system can proactively support athletes to successfully meet the ever-increasing demands of top-level professional sport is less prevalent. This study takes advantage of a naturally occurring but highly atypical developmental challenge as a result of COVID-19 to examine factors influencing the efficacy and effectiveness of the talent development pathway at Munster Rugby. Players and staff (n = 12) took part in semi-structured interviews exploring their experiences of the build-up to the event, the game itself, and the impact post-event. The data were subsequently analysed using Reflexive Thematic Analysis. Players and coaches highlight the groundwork undertaken to establish alignment and coherence, both horizontally and vertically across the talent development environment, and how this contributed to navigating the challenge successfully. The findings support the necessity of both the player and the talent development system being prepared to enable players to perform at the highest level. The findings point to an overlap between the development and performance phases of a player's journey and the need to integrate short- and long-term objectives within a talent development system.